Study of metformin in polycystic ovary syndrome - Mehta, Heeta R.; Shah, Sushma R.; Mehta, Ami V.; Panchal, Payal P. (International Journal of Research in Medical Sciences, 2022)
Background: Objective of the study was to measure the efficacy and safety of insulin sensitizing drug metformin in reversing the metabolic and endocrine disturbances in fifty women with polycystic ovarian disease. Methods: The study was performed on 57 women with polycystic ovarian syndrome (PCOS) in the outpatient department of obstetrics and gynaecology, V. S. General Hospital, Ahmedabad. Metformin 500 mg thrice daily was given until the cysts disappeared which was taken as the end point of the study. Follicular studies were done to check the effect of metformin on ovulation. Significance was tested by paired t test and p value calculated. Results: Metformin was found effective in regressing polycystic changes in ovary, regularization of menstrual cycles and improving ovulation. Conclusions: The present study shows that metformin has a beneficial role in effective management of PCOS.